Оцінка стоматологічного статусу у дітей із патологією зубо-щелепової системи і міофункціональними порушеннями на тлі вивчення функціональної системи дихання = Evalution of the dental status of children with disorders of the teeth-jaw system and miofunctional violations against a background study of functional respiratory system - Drogomyrec'ka, M. S.; Salama, Ahmad Saleh Haljaf; Poljanyk, N. Ja.; Jakymec, A. V. (Journal of Education, Health and Sport, 2017)
Drogomyrec'ka M. S., Ahmad Saleh Haljaf Salama, Poljanyk N. Ja., Jakymec A. V. Оцінка стоматологічного статусу у дітей із патологією зубо-щелепової системи і міофункціональними порушеннями на тлі вивчення функціональної системи дихання = Evalution of the dental status of children with disorders of the teeth-jaw system and miofunctional violations against a background study of functional respiratory system. Journal of Education, Health and Sport. 2016;6(11):557-564. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.197101 http://ojs.ukw.edu.pl/index.php/johs/article/view/4050 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.11.2016. Revised 22.11.2016. Accepted: 30.11.2016. УДК 616.31.003.121-053.2/.6+(616-007+616.314+616.716.8) ОЦІНКА СТОМАТОЛОГІЧНОГО СТАТУСУ У ДІТЕЙ ІЗ ПАТОЛОГІЄЮ ЗУБО-ЩЕЛЕПОВОЇ СИСТЕМИ І МІОФУНКЦІОНАЛЬНИМИ ПОРУШЕННЯМИ НА ТЛІ ВИВЧЕННЯ ФУНКЦІОНАЛЬНОЇ СИСТЕМИ ДИХАННЯ М. С. Дрогомирецька, Ахмад Салех Халяф Салама, Н. Я. Поляник, А. B. Якимець Інститут стоматології НМАПО ім. П. Л. Шупика Резюме Вступ. Функціональні розлади дихання, ковтання, жування, мовлення, а також аномалійний розвиток твердих і м'яких тканин порожнини рота ведуть до порушення зубощелепної системи. Морфологічні порушення розвитку зубощелепної системи поєднуються зі значними функціональними дисфункціями. Вони, в свою чергу, створюють несприятливі умови для збереження стійкості зубощелепної системи до фізіологічних навантажень. Мета. Вивчення стану функціональної системи дихання у дітей 3-6 років із патологією зубощелепної системи та міофункціональними порушеннями. Методи дослідження. Стан функціональної системи дихання оцінювали методом спірографії у 54 пацієнтів 3-6 років, із яких у 19 ‑ із міофункціональними порушеннями (дослідна група) та у 35 - без міофункціональних порушень (контрольна група) апаратом "Метатест-1". При аналізі спірограм обчислювалася частота дихання, дихальний об'єм, хвилинний об'єм дихання, резервний обсяг вдиху та видиху, життєву та форсовану життєву ємкість легень та індекс Тифно. Результати. У дітей з різцевою дизоклюзією зубних рядів встановлено зниження статичних та динамічних показників зовнішнього дихання. Висновки. Пацієнти, які знаходяться під наглядом лікаря-ортодонта з діагнозом різцевої дизоклюзії зубних рядів та мі функціональними порушеннями, потребують включення до плану лікування не тільки апаратурного методу корекції аномалії, але й без апаратурного, а саме, проведення дихальної гімнастики. Ключові слова: функціональна система дихання, міофункціональні порушення, зубощелепна система. EVALUATION OF THE DENTAL STATUS OF CHILDREN WITH DISORDERS OF THE TEETH-JAW SYSTEM AND MIOFUNCTIONAL VIOLATIONS AGAINST A BACKGROUND STUDY OF FUNCTIONAL RESPIRATORY SYSTEM M. S. Drogomyrec'ka, Ahmad Saleh Haljaf Salama, N. Ja. Poljanyk, A. V. Jakymec Institute of Dentistry P. L. Shupik National Medical Academy of Post Graduate Education, Kiev, Ukraine dr.myroslava@gmail.com Summary Introduction. Functional disorders of breathing, swallowing, chewing, speaking, and developmental anomalies of hard and soft oral tissues leading to a breach dentition have been analyzed. Morphological developmental disorders dentition are combined with significant functional dysfunction. They, in turn, create unfavorable conditions for maintaining stability dentition to physiological stress. The objective. To study the functional system of breathing in children aged 3-6 y. o. with pathology of teeth-jaw system and miofunctional disorders. Research methods. Functional status of the respiratory system was evaluated spirographically in 54 patients aged 3-6 y. o. 19 of them had miofunctional disorders (experimental group) and 35 had none (control group). Apparatus "Metatest-1" was used. In the spirograms under analysis respiratory rate, tidal volume, respiratory minute volume, inspiratory reserve volume and expiration, vital capacity and forced vital lung and Tyfno index were calculated. Results. The with incisive disocclusion children set dentition reduce static and dynamic performance of external breathing. Conclusions. The patients who are under medical supervision of orthodontist with diagnosed incisive disocclusion dentition and functional disorders require the treatment plan including not only hardware method of anomalies correction, but apparatus-free ones, namely, breathing exercises. Key words: functional respiratory system, miofunctional disorder, tooth-jaw system.